Hubungan antara riwayat status gizi ibu masa kehamilan dengan pertumbuhan bayi usia 9-12 bulan - Rilyani Rilyani; Lelly Sugiyati (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Maternal nutritional status during pregnancy and effects on growth among infants 9-12 monthsBackground: Maternal nutritional status during pregnancy needs attention because it affects the development of the fetus they are carrying. During pregnancy are at risk of experiencing of chronic energy deficiency (CED) in adults if they have LILA <23.5 cm are at risk of maternal death, preterm delivery/low birth weight (LBW), death and impaired growth and development of infant. Base on data in Way Panji Public Health Centre reported that among maternal during pregnancy were of 43 (29.05%) who has LILA <23.5 cm.Purpose: To determine the relationship between maternal nutritional status during pregnancy and infant growth at the Way Panji Community Health Centre coverage area.Method: A quantitative by cross-sectional research, the population in this study were of 143 respondent as all maternal who had an infant aged 9-12 months in May 2020. Both of them observed such as a history of maternal nutritional status during pregnancy and infant growth when aged 9-12 months and bivariate analysis (Chi-Square).Results: Showing that the frequency distribution of maternal nutritional status during pregnancy, mostly with has sufficient in nutrition of 113 (79.0%) respondents and they have an infant with a normal growth of 107 (74.8%). There is a relationship between maternal nutritional status during pregnancy and infant growth (p-value 0.000: OR 5,314).Conclusion: There is a relationship between maternal nutritional status during pregnancy and infant growth in Way Panji Public Health Center coverage area Lampung-Indonesia. Suggestions to public health centre management to increase the promotion programme of maternal nutritional status during pregnancy and preventing poor growing of the infant by providing leaflets or posters also supplement nutritions for maternal during pregnancy.Keywords: Maternal; Nutritional status; Pregnancy; Infant; GrowthPendahuluan: Gizi ibu hamil perlu mendapat perhatian karena sangat berpengaruh pada perkembangan janin yang dikandungnya, Wanita hamil berisiko mengalami KEK jika memiliki LILA < 23,5 cm. ibu hamil dengan KEK berisiko melahirkan bayi berat lahir rendah (BBLR). BBLR akan membawa risiko kematian, dan gangguan pertumbuhan dan perkembangan anak. KEK juga dapat menjadi penyebab tidak langsung kematian ibu. Data dari Puskesmas Way Panji mengatakan bahwa terdapat 43 orang (29,05%) yang berisiko KEK dengan LILA < 23,5 cm.Tujuan: Diketahui Hubungan Status Gizi Ibu Masa Kehamilan Dengan Pertumbuhan Bayi Di Puskesmas Way Panji Kecamatan Way Panji Kabupaten Lampung Selatan Metode: Jenis penelitian kuantitatif dengan menggunakan metode penelitian crossectional , Subyek dalam penelitian ini adalah Ibu Masa Kehamilan, Variabel dependen : Pertumbuhan bayi, variabel independent : gizi ibu saat hamil, populasinya paraibu yang telah melahirkan dan bayinya usia 9-12 bulan dengan total sampel berjumlah 143 responden/bayi, dilakukan pada bulan Juli-Agustus 2020, dengan analisa univariat dan bivariat (Chi-Square).Hasil: Didapatkan Distribusi frekuensi status gizi ibu masa kehamilan, sebagian besar dengan gizi baik yaitu sebanyak 113 (79,0%) responden. pertumbuhan bayi kategori normal yaitu sebanyak 107 (74,8%). Ada hubungan status gizi ibu masa kehamilan dengan pertumbuhan bayi (p-value 0.000 : OR 5,314).Simpulan: Ada hubungan status gizi ibu masa kehamilan dengan pertumbuhan bayi di Puskesmas Way Panji, Disarankan kepadapihak manajemen Puskesmas setempat supaya dapat meningkatan upaya promosi guna penurunan kejadian pertumbuhan bayi yang abnormal dan membantu terpenuhinya kebutuhan gizi atau nutrisi pada saat ibu dalam masa kehamilan dengan cara pemberian leaflet atau poster.